Entre a qualificação profissional e a formação cidadã: um árido desafio para o PNQ/PlanTeQ na Paraíba - Carvalho, Rejane Gomes (2011)
The aim of this work is to study the policy of professional qualification in the state of Paraíba based on the National Plan of Qualification and the Territorial Plan of Qualification - PNQ/PlanTeQ, in the period between 2003 and 2010, trying to investigate, mainly, the capacity these programmes have to simultaneously suit the immediate necessities of professional and orientational qualification to the citizen formation of the subjects, in a context of unemployment in the labour world. In face of the conjuncture of transformations in the dimensions of politics and work since 1990, marked by the expansion of the globalization process of the economy, by the flexible production and by the reform of the state, new social demands are now part of the social questions with the increase of unemployment and poverty. The public policy of employment needed to be reformulated in a way to intensify its role in the intermediation and the professional formation of the workers, as an strategy to face the problem of social exclusion by work. The PNQ/PlanTeQ-Paraíba considers the professional qualification as a right to citizenship and public policy, and this is why it is pertinent to analyse how the students percieve themselves in this process and if the courses offered are forming workers with capacity and competence in conditions of insertion in the labour market, at the same time it proposes to form citizens who are critical and conscious of their place in society. It is in this context of redefinition of the public policies, more specifically with the PNQ and the PlanTeQ-Paraíba, that the analysis of the basis of the conception and objectives of professional qualification is proposed, especially on how it articulates the professional qualification with the citizen formation; to identify the main actors involved in the construction and management of the PlanTeQ-Paraíba and the relations of the forces established among them; and also to investigate the processes to define plans of action of the PlanTeQ-Paraíba in relation to the conditions of execution, focusing on the contents to be dealt with and the profile of the people responsible for its execution, principally considering the ways to make the professional qualification and the citizen formation compatible. The main methodological resources used were the bibliographical and documental formation, observation of participants and field research. To the latter, interviews were done with some of the various subjects who act in the management and execution of the PlanTeQ in Paraíba, observations in the meetings of CETE-Paraíba and the participation in professional qualification courses, besides the realization of a focus group with students of a professionalization course, that made the reunion of a rich qualitative material possible, privileging the critical analysis of objective and subjective elements which permeate the deployment of PlanTeQ in the state. A perspective of apprehending the public policy as a process in construction, with advances, permanence or setbacks, in which the struggle and dispute of power and social places is common is adopted. To be expressed as a right to citizenship and to be able to guarantee its effectiveness, we understand that the policy of professional qualification must be an integral part of a wider project of social insertion, being tuned with a set of social policies to, besides giving the professional formation, make the universal rights and the possibility of a social construction to an active citizenship possible to the subject.